Effects of group music therapy on depressive symptoms in women [data] - Gäbel, Christine; Stoffel, Martin; Aguilar-Raab, Corina; Jarczok, Marc N.; Rittner, Sabine; Ditzen, Beate; Warth, Marco (Universität, 2024)
Abstract Background. Music directly addresses the emotions and other functional systems that are impaired in major depressive disorder (MDD). Therefore, music therapy (MT) can be an effective complement in the treatment of MDD. To date, the research situation is not sufficient to provide evidence of its efficacy. Methods. The study was conducted as a randomized controlled trial with group MT (GMT) in the intervention group (IG) and a waitlist control group (CG). The study aimed to investigate group*time interaction effects regarding self-rated, observer-rated, and momentary depression. Secondary outcomes encompassed emotion and mood regulation strategies and health-related quality of life. Outcomes were measured before, after, and partly 10 weeks after the intervention period. Results. 102 women between 18 and 65 years diagnosed with current MDD took part in the study. Overall, greater health-promoting effects were shown in the IG than in the CG, particularly in the pre-to-post comparison. Significant results were shown regarding momentary depression, quality of life, and different regulation strategies, especially using music. Limitations. Limitations comprised the high dropout rate and data loss due to the coronavirus pandemic, long-term effects of GMT not being assured, limited generalizability due to the biological female sex of the sample, and conditional transferability due to the process-driven application of GMT. Conclusions. GMT is a cost-effective and non-invasive approach to treat MDD yielding health-promoting effects regarding depressive symptoms, regulatory abilities, and QoL. However, the underlying mechanisms of action should be further investigated within methodologically high-quality studies. For this purpose, manualization of MT is strongly recommended. Trial Registration: The MUSED study was pre-registered in the German Clinical Trials Register (registration code: DRKS00016616). (2023-10-29)